Neuroproteção fornecida por docosanoides: uma nova estratégia terapêutica no AVC isquêmico experimental - Roque, Cássia Rodrigues (2023)
Acute ischemic stroke triggers complex neurovascular, neuroinflammatory and synaptic changes. Neuroprotection to attenuate or block the ischemic cascade and save neuronal damage has been extensively explored in the treatment of ischemic stroke. However, despite increasing knowledge of regulatory, mechanistic, and imaging characterizations of ischemic penumbra, no effective neuroprotective therapy has been found. We tested the hypothesis whether the administration of LAU-0901 and some selected docosanoids (DHA, NPD1, AT-NPD1 and RvD1) in monotherapy or in combination, after middle carotid artery occlusion (MCAo), would lead to neurological recovery. Male Sprague-Dawley rats received were protected by MCAo and after the period established by the experimental series performed (between 2 and 6 h) the substances were administered. Behavioral tests, ex vivo MRI and lipidomic analysis were performed a few days later to assess the lesion characteristics. Series 1 was divided into three protocols: (LAU‑0901+NPD1, 14d), (LAU‑0901+AT‑NPD1, 3d) and (LAU‑0901+DHA, 1d). In series 2 and 3, dose-response and therapeutic window studies were carried out, respectively, for LAU, NPD1 and AT-NPD1, and RvD1 and NPD1, alone or combined and at different dosages. In series 1 it was observed that combinatorial groups improved behavior compared to NPD1, AT‑NPD1 or DHA treatments alone. Total lesion volumes were reduced with LAU‑0901+NPD1 by 62% and LAU‑0901+AT‑NPD1 by 90% of treatments versus vehicle groups. LAU‑0901 and LAU‑0901+DHA increased the production of vasoactive lipid mediators (prostaglandins: PGE2, PGF2‑α, 6‑keto‑PGF1‑α and PGD2), as well as an inflammatory regulatory mediator hydroxyoctadecadienoic acid. In contrast, LAU‑0901 and LAU‑0901+DHA decreased the production of 12‑hydroxyeicosatetraenoic acid, a pro‑inflammatory mediator. In series 2, LAU and AT-NPD1 treatments alone improved behavior by 40–42% and 20–30%, respectively, and LAU+AT-NPD1 by 40% compared to the vehicle group. T2-weighted image volumes (T2WI) were reduced with all doses of LAU and AT-NPD1 by 73–90% and 67–83% and LAU+AT-NPD1 by 94% compared to vehicle. In the therapeutic window, LAU+AT-NPD1, when given at 3, 4, 5, and 6 hours, improved behavior by 50, 56, 33, and 26% and included T2WI volumes by 93, 90, 82, and 84% compared to vehicle. With series 3 we demonstrated that treatment with NPD1, RvD1 and combined therapy provides high-grade neurobehavioral recovery and decreases ischemic core and penumbra volumes even when administered up to 6 hours after stroke. Therapy with a platelet activating factor receptor antagonist, LAU‑0901, and the use of selected docosanoids is more effective than therapy alone, providing synergistic neuroprotection, with restorative, prohomeostatic lipid mediators and improved neurological recovery. Taken together, our findings support combination therapy as the basis for future ischemic stroke therapies.